Pedagogical practice based on the dimensions of work and cultural identity in schools in the communities of the Tocantina Amazon - Hellen do Socorro de Araujo Silva; Benedito Junior dos Prazeres Silva (Universidade Federal do Norte do Tocantins, 2024)
This is a study carried out in the Tocantina Amazon, with the aim of analyzing the pedagogical practice of teachers/graduates of the Degree in Field Education in the Countryside - LEDOC, in dialogue with the lives of the subjects in the communities, based on the dimensions of work and cultural identity. It was based on a qualitative approach, and its methodological procedures included field research using participant observation and semi-structured interviews. The results revealed that LEDOC graduates, when working in schools in the countryside, waters and forests, have sought to dialog with aspects of the territory, work and identity of the subjects, despite the difficulties faced in their socio-professional insertion.